2021
DOI: 10.1155/2021/4023472
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of the Combination of Platelet Count with Neutrophil-to-Lymphocyte Ratio in Aged Patients with Acute Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: Background and Aim. Acute myocardial infarction represents the vital cause of cardiac death, and many measurable biomarkers have been reported to be related to the prognosis of acute myocardial infarction. Our study was to investigate the role of a novel biomarker, the combination of platelet count, and neutrophil-to-lymphocyte ratio, for predicting in-hospital and long-term mortality of aged patients with acute myocardial infarction. Method. This was a study recording 637 patients who were diagnosed with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…respectively. Out of 35 observational studies, there were 34 retrospective or prospective studies [12–45] and 1 cross-sectional study. [46] These 35 observational studies enrolled a total population of 28,756 participants, out of which 9678 patients had high NLR and 13,105 patients had low NLR, while one study didn’t specify high NLR and low NLR participants.…”
Section: Resultsmentioning
confidence: 99%
“…respectively. Out of 35 observational studies, there were 34 retrospective or prospective studies [12–45] and 1 cross-sectional study. [46] These 35 observational studies enrolled a total population of 28,756 participants, out of which 9678 patients had high NLR and 13,105 patients had low NLR, while one study didn’t specify high NLR and low NLR participants.…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiologic mechanism of different etiologies of MINOCA has been described, including atherosclerotic plaque disruption, coronary vasospasm, microvascular dysfunction, spontaneous coronary dissection, and supply-demand imbalance [ 2 , 6 ]. The potential role of inflammation in the etiology of CAD, atherosclerotic coronary plaque instability, and thrombus formation has been established earlier [ 30 , 31 ]. The components of complete blood count and the derived parameters, particularly WBC count, MPV, WMR, NPR, NLR, and PLR, have been evaluated as inflammation risk factors to explore their role and predictive ability in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies [12,13] had shown that a decreased platelet count was associated with the severity of MI, death and reinfarction. However, the relationship between platelet counts and the prognosis of MI was controversial [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%